2014
DOI: 10.1007/s00261-014-0200-3
|View full text |Cite
|
Sign up to set email alerts
|

Value of gadoxetate biliary transit time in determining hepatocyte function

Abstract: The transit time for gadoxetate to appear in extrahepatic duct is a reasonable indicator of liver function, and may be included in radiology reports. The appearance in the duodenum, however, may depend on factors other than liver function, such as the physiology of the gallbladder and sphincter of Oddi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(35 reference statements)
0
5
1
Order By: Relevance
“…In the present study, 95% of the patients in the non-cirrhosis group (35/37) had the IBD visualized within 10 min after the administration of Gd-EOB-DTPA. Only 54.2% of cirrhotic patients (CP A + CP B) (38/70) had the IBD visualized within 10 min after the administration, which was slightly lower than that reported by Wu et al ( 7 ) (65.4%). The reason may be that the proportion of CP A group patients in the cirrhotic patients (CP A + CP B) in our study is relatively lower than that in the study of Wu et al (57.1% vs. 63.1%).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In the present study, 95% of the patients in the non-cirrhosis group (35/37) had the IBD visualized within 10 min after the administration of Gd-EOB-DTPA. Only 54.2% of cirrhotic patients (CP A + CP B) (38/70) had the IBD visualized within 10 min after the administration, which was slightly lower than that reported by Wu et al ( 7 ) (65.4%). The reason may be that the proportion of CP A group patients in the cirrhotic patients (CP A + CP B) in our study is relatively lower than that in the study of Wu et al (57.1% vs. 63.1%).…”
Section: Discussioncontrasting
confidence: 55%
“…For the detection of liver lesions, patients with impaired liver function often need a longer time to increase the uptake of Gd-EOB-DTPA by liver parenchyma. Furthermore, recent studies have indicated that the timing of the initial visualization of the IBD is intrinsically associated with the liver function, the better the liver function, the earlier the initial visualization of the IBD after the administration ( 7 , 23 ). Consequently, the visualization of the IBD is utilized in optimizing the HCP acquisition protocol as one of the preconditions for consideration of an adequate HCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,1317 A series of studies have also monitored the time course of contrast agent accumulation and appearance in the biliary system and gallbladder (eg, hepatobiliary transit times) as a means to characterize the biliary ductal system. 1820 …”
mentioning
confidence: 99%
“…ExiTron is advised to be used in longitudinal monitoring with repeated injections, and Primovist (Gd-EOB-DTPA) is a new hepatocyte-specific contrast agent for MRI of the liver. Compared to extracellular contrast agents, Primovist shows a partial specific uptake by hepatocytes followed by a subsequent biliary excretion [79,80]. …”
Section: Assessment Techniquesmentioning
confidence: 99%